Escolas do campo: uma proposta de valorização cultural por meio das práticas de letramento - Martins, Daiane Aparecida (2019)
Field education arose from social movements and the need to adopt a teaching that valued the yearnings, needs and culture of the peasant population, aspects that were not considered in the existing rural education model. Rural education for many years emphasized the formation of labor and the generation of profits from the land, besides being treated without any priority by the public power, so the proposed study aims to promote reflections on this history, as well as to value the peasant culture through literacy and multiliteracies practices, allied to the study of textual genres. The action research method used gave rise to a textual genre study material entitled “I, My Culture and the land,” which was applied in a rural school and reported as part of this research. In the final phase, regarding the results, I found that a contextualized study in Portuguese language classes was able to promote culture and cause a greater interest in the students, who felt valued for studying textual genres and themes consistent with their social practices.